The influence of vegetation cover on the grain-size distributions and thicknesses of two Icelandic tephra layers ... - Morison, Conner A. G.; Streeter, Richard T. (My University, 2022)
This dataset accompanies the paper of the same title. Grain-size distributions and thicknesses of tephra layers are used to reconstruct characteristics, dynamics and hazards of explosive volcanic eruptions, but the extent to which the preservation of tephra is influenced by depositional environments is unclear. This paper analyses grain-size distributions and thicknesses of tephra layers produced by the Eyjafjallajökull (2010) and Grímsvötn (2011) eruptions. We collected 110 tephra samples and layer thickness measurements from 86 sites at two locations in southern Iceland. Areas of different vegetation cover have varying capacities to affect rates of tephra erosion, retain fallout or capture remobilised tephra. The G2011 tephra was somewhat coarser-grained and thicker in areas of birch woodland than in adjacent moss heath, but no comparable differences in the Ey2010 tephra were observed. The spatial variability (over tens of metres) of median particle-size and layer thickness is low, providing confidence ... : Morison_and_Streeter_2022_binned_volumes_of_tephra_samples.csv Morison_and_Streeter_2022_key_metrics_of_tephra_samples.csv Morison_and_Streeter_2022_accompanying_metadata_for_repository.docx ...